2011
DOI: 10.1029/2011ja016645
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence associated with corotating interaction regions at 1AU: Inertial range cross-helicity spectra

Abstract: [1] We examine five corotating interaction regions and their surrounding slow and fast wind flows observed by the Advanced Composition Explorer spacecraft at 1 AU during solar minimum conditions in 2007 and 2008. We compute spectra of total power (magnetic + kinetic) and spectra of the cross helicity in an attempt to better understand turbulence generation within the shear flow. Consistent with previous work, we find that Sunwardpropagation signatures exist at high levels compared with the surrounding flow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 38 publications
3
20
1
Order By: Relevance
“…Grappin et al [1990] found that particularly inward fluctuations are enhanced by compression, while Bruno and Bavassano [1993] found density and magnetic field fluctuations to destroy the correlation between the velocity and magnetic field. Also, velocity shear in the stream interaction region can transfer energy to the fluctuations creating large amplitude inward and outward fluctuations [Coleman Jr., 1968;Smith et al, 2011]. All these are consistent with the high B Z we observe for low Alfvénicity in the leading part.…”
Section: Alfvénicity In the Solar Windsupporting
confidence: 87%
“…Grappin et al [1990] found that particularly inward fluctuations are enhanced by compression, while Bruno and Bavassano [1993] found density and magnetic field fluctuations to destroy the correlation between the velocity and magnetic field. Also, velocity shear in the stream interaction region can transfer energy to the fluctuations creating large amplitude inward and outward fluctuations [Coleman Jr., 1968;Smith et al, 2011]. All these are consistent with the high B Z we observe for low Alfvénicity in the leading part.…”
Section: Alfvénicity In the Solar Windsupporting
confidence: 87%
“… Borovsky and Denton [2010] argue there is no evidence of shear‐induced turbulence. We must disagree with this statement and offer evidence contrary to our companion paper [ Smith et al , 2011]. The analysis of Horbury and Schmidt [1999] also discounts this interpretation.…”
Section: Introductioncontrasting
confidence: 69%
“…Waves upstream of shocks are a good example of the former situation [ Lee , 1983] while the general absence or difficulty in finding waves due to interstellar pickup ions in the outer heliosphere [ Lee and Ip , 1987; Murphy et al , 1995; Isenberg , 1995] is a good example of the latter dynamic. Smith et al [2011] show distinct signatures of energy injection within the cross helicity spectra, but finds no clear evidence for wave injection within the power spectrum.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This avoids the complications associated with third-moment expressions that are applicable to shear regions [117][118][119]. It also fails to address questions of in situ generation of turbulence in these regions [120][121][122]. As with our earlier papers, we interpolate the results of each 1 h sample onto a common spatial grid that is equivalent to measurements with a 400 km s −1 wind speed.…”
Section: Discussionmentioning
confidence: 99%